Etika Komunikasi Antara Guru dan Murid: (Studi Pemikiran Imam Al-Ghazali dalam Karya Bidayatul Hidayah) - Ega Nurhasanah; Rodliyah Khuza’I; Sausan M. Sholeh (Bandung Conference Series: Islamic Broadcast Communication, 2022)
Abstract. Good communication ethics will result in effective learning. In the book Bidayatul Hidayah by Imam Al-Ghazali explained some teacher and student ethics that must be applied in the learning process. The purpose of this study was to determine the ethics of communication between teachers and students according to Imam Al-Ghazali, its relevance to the ethics of Islamic religious communication, and the implications for future generations. This study uses a qualitative type with descriptive-analytical method and uses interpersonal communication theory. The data was obtained through the book Bidayatul Hidayah, secondary data, other relevant books and internet media. The results of the study found that first, there were seventeen teacher ethics and thirteen student ethics in the book Bidayatul Hidayah. Second, the ethics of Islamic religious communication is relevant to the communication ethics of Imam Al-Ghazali. Third, the ethical implications of Imam Al-Ghazali's communication for future generations will certainly be very helpful in the communication process. Communication ethics can produce more effective communication when applied. Abstrak. Etika komunikasi yang baik akan menghasilkan pembelajaran yang efektif. Dalam kitab Bidayatul Hidayah karya Imam Al-Ghazali dijelaskan beberapa etika guru dan murid yang harus diterapkan dalam proses pembelajaran. Tujuan penelitian ini untuk mengetahui etika komunikasi antara guru dan murid menurut Imam Al-Ghazali, relevansi dengan etika komunikasi agama Islam, serta implikasi bagi generasi yang akan datang. Penelitian ini menggunakan jenis kualitatif dengan metode deskriptif-analitis serta menggunakan teori komunikasi antarpersonal. Data diperoleh melalui kitab Bidayatul Hidayah, data sekunder, buku lain yang relevan serta media internet. Hasil penelitian menemukan Pertama, terdapat tujuh belas etika guru dan tiga belas etika murid dalam kitab Bidayatul Hidayah. Kedua, etika komunikasi agama Islam relevan dengan etika komunikasi Imam Al-Ghazali. Ketiga, Implikasi etika komunikasi Imam Al-Ghazali bagi generasi yang akan datang tentu akan sangat membantu dalam proses komunikasi. Etika komunikasi dapat menghasilkan komunikasi yang lebih efektif apabila diaplikasikan.